van der Waals-induced chromatic shifts in hydrogen-bonded two-dimensional porphyrin arrays on boron nitride - Korolkov, Vladimir V.; Svatek, Simon A.; Summerfield, Alex; Kerfoot, James; Yang, Lixu; Taniguchi, Takashi; Watanabe, Kenji; Champness, Neil R.; Besley, Nicholas A.; Beton, Peter H. (American Chemical Society, 2015)
The fluorescence of a two-dimensional supramolecular network of 5,10,15,20-tetrakis(4-carboxylphenyl)porphyrin (TCPP) adsorbed on hexagonal boron nitride (hBN) is red shifted due to, primarily, adsorbate–substrate van der Waals interactions. TCPP is deposited from solution on hBN and forms faceted islands with typical dimensions of 100 nm and either square or hexagonal symmetry. The molecular arrangement is stabilized by in-plane hydrogen bonding as determined by a combination of molecular resolution atomic force microscopy performed under ambient conditions and density functional theory; a similar structure is observed on MoS2 and graphite. The fluorescence spectra of submonolayers of TCPP on hBN are red-shifted by ∼30 nm due to the distortion of the molecule arising from van der Waals interactions, in agreement with time-dependent density functional theory calculations. Fluorescence intensity variations are observed due to coherent partial reflections at the hBN interface, implying that such hybrid structures have potential in photonic applications.